Inquiry Learning with Polya Proplem Solving to Improve Student Learning Outcomes and Engagement - Farid Gunadi; Khofifah Khofifah; Luthfiyati Nurafifah; Asep Maolana Akbar (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
Abstract: This study aims to determine whether students' engagement with trigonometry material may be increased through inquiry learning by solving Polya problems. The classroom action research approach is used in this study. 36 pupils from class X, MIPA 7, SMA 1, Indramayu, served as the subjects for this study. In this study, only two cycles are allowed. The findings from cycle I revealed that not all group members could effectively communicate with one another when trying to solve a problem. Another issue with the teacher is that he has not been able to manage his time well, which results in his spending a lot of time explaining the content. s a result, learning's primary objective—which requires pupils to be more engaged and solve their own problems—is not adequately achieved. However, it appears that the specified performance indicators have been met based on the findings of teacher and student observations made during the second cycle of action.Keywords: